Waste analysis of coated peanut production using fuzzy analytical hierarchy process (Fuzzy AHP) - Erika Ayu Yuanita; Panji Deoranto; Arif Hidayat; Riska Septifani; Wendra Gandhatyasri Rohmah (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Production effectiveness is an essential aspect of industrial activities to obtain maximum profit with minimum expenditure. One of the companies currently focused on achieving high effectiveness in its production activities is PT XYZ. The purpose of the study was to determine the priority of waste in the coated peanut processing company using the Fuzzy Analytical Hierarchy Process (Fuzzy AHP) method. The Fuzzy AHP method combines AHP with a fuzzy system to cover the weaknesses of AHP, which has more personal properties. The Fuzzy AHP method helps in identifying the level of waste in PT XYZ, which is grouped into seven, namely defects (S1), waiting (S2), unnecessary inventory (S3), inappropriate processing (S4), unnecessary motion (S5), transportation (S6), and overproduction (S7). The results showed that the order of wastage criteria starting from the highest to the lowest are S4 with a weight vector value of 1,000; S5 with a weight vector value of 0,985; S1 with a weight vector value of 0,932; S2 with a weight vector value 0,702; S6 with weight vector value 0,678; S3 with a weight vector value 0,144; S7 with weight vector value 0,071. Based on this, it can be seen that the criteria for inappropriate processing have the highest priority as waste in production activities at PT XYZ. The results of the Fuzzy AHP method can be used as a basis for weighting the value stream analysis tools.